Impacto da mastite subclínica na reprodução de vacas leiteiras - Barbosa, Lucas Furtado dos Santos Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Os objetivos destes estudos foram (1) determinar a sensibilidade (Se.) e especificidade (Sp.) de diferentes limiares de CCS para identificar mastite subclínica; (2) verificar o impacto do isolamento de bactérias causadoras de mastite e da CCS durante protocolo de transferência de embriões em tempo fixo (TETF) na P/TE de vacas em lactação. No Exp.1, 2.516 vacas Holandesas e Girolando (8 fazendas), foram submetidas a coleta de duas amostras de leite para análise de CCS e cultura microbiológica para determinar o crescimento bacteriano. No Exp.2, 1.397 vacas Girolando em lactação foram submetidas a um protocolo de TETF. Amostras de leite foram coletadas dois dias antes da TETF para cultura microbiológica e análise de CCS. O diagnóstico de gestação foi realizado nos dias 31 e 66. Os animais foram divididos de acordo com o isolamento apresentado, em 5 grupos experimentais segundo recomendações do “national mastitis council” (NMC): Gram-positivas ambientais (AB+; Bacillus spp., Enterococcus spp., Streptococcus spp, Micrococcus spp.,), Gram-negativas ambientais (AB-; Citrobacter freundii, Coliformes, Enterobacter spp., Klebsiella spp., Proteus spp., Pseudomonas spp.), Gram-positivas contagiosas (C+; Corynebacterium bovis, Staphylococcus aureus, Streptococcus agalactiae), SCN (Estafilococos coagulase negativa) e...

The objectives of these studies were (1) determine the sensitivity (Se) and specificity (Sp) of different SCC thresholds to identify subclinical mastitis, (2) assess the impact of microorganism causative of mastitis and SCC during fixed-time embryo transfer (FTET) protocol in P/ET in dairy cows. In study 1, 2516 Holstein and Girolando cows (8 farms) were enrolled. Two composite milk samples were collect from each cow, one for SCC analysis and other for bacteriological analysis. In study 2, 1397 Girolando lactating cows were subjected to a FTET. Milk samples were collected two days before the ET for bacteriological analysis and SCC. Pregnancy diagnosis was performed on days 31 and 66. The animals were split according to the bacterial growth in 5 experimental groups according to the recommendations of the National Mastitis Council (NMC): Gram-positive environmental (AB +; Bacillus spp., Enterococcus spp., Streptococcus spp, Micrococcus spp.), Gram-negative environmental (AB-, Citrobacter freundii, Coliforms, Enterobacter spp., Klebsiella spp., Proteus spp., Pseudomonas spp.), Gram-positive contagious (C+; Corynebacterium bovis, Staphylococcus aureus, Streptococcus agalactiae), CNS (coagulase-negative staphylococci) and control (no bacteria growth). In experiment 1, three SCC thresholds (100,000, 200,000 and 400,000 cells/ml) were used to determine the Se. and Sp. in detect intramammary infection (IMI). The CNS were grouped with the control group for the analysis of study 2 because the growth of these agents is not usually associated with mammary gland disease. The cows were also classified into three groups according to the SCC: less than 200,000 cells/ml, between 200,000 and 400,000 cells/ml, and greater than 400,000 cells/ml. SAS PROC GLIMMIX was used for statistical analysis. For analysis P <0.05 was... (Complete abstract click electronic access below)
Keywords: Bovino de leite; Reprodução animal - Aspectos nutricionais; Produção animal; Mastite - Bovino; Embryos - Nutrition